CD73+ extracellular vesicles inhibit angiogenesis through adenosine A2B receptor signalling. Issue 1 (4th May 2020) - Angioni, Roberta; Liboni, Cristina; Herkenne, Stephanie; Sánchez‐Rodríguez, Ricardo; Borile, Giulia; Marcuzzi, Elisabetta; Calì, Bianca; Muraca, Maurizio; Viola, Antonella
ABSTRACT: Pathological angiogenesis is a hallmark of several conditions including eye diseases, inflammatory diseases, and cancer. Stromal cells play a crucial role in regulating angiogenesis through the release of soluble factors or direct contact with endothelial cells. Here, we analysed the properties of the extracellular vesicles (EVs) released by bone marrow mesenchymal stromal cells (MSCs) and explored the possibility of using them to therapeutically target angiogenesis. We demonstrated that in response to pro‐inflammatory cytokines, MSCs produce EVs that are enriched in TIMP‐1, CD39 and CD73 and inhibit angiogenesis targeting both extracellular matrix remodelling and endothelial cell migration. We identified a novel anti‐angiogenic mechanism based on adenosine production, triggering of A2B adenosine receptors, and induction of NOX2‐dependent oxidative stress within endothelial cells. Finally, in pilot experiments, we exploited the anti‐angiogenic EVs to inhibit tumour progression in vivo . Our results identify novel pathways involved in the crosstalk between endothelial and stromal cell and suggest new therapeutic strategies to target pathological angiogenesis.